2014
DOI: 10.1158/1055-9965.epi-14-0281
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Africa 2012

Abstract: Background: Noncommunicable diseases, and especially cancers, are recognized as an increasing problem for low and middle income countries. Effective control programs require adequate information on the size, nature, and evolution of the health problem that they pose.Methods: We present estimates of the incidence and mortality of cancer in Africa in 2012, derived from "GLOBOCAN 2012," published by the International Agency for Research on Cancer.Results: There were 847,000 new cancer cases (6% of the world total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
288
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(308 citation statements)
references
References 65 publications
(67 reference statements)
7
288
0
13
Order By: Relevance
“…Owing to the potentially multifactorial complexity of anemia, defining causes in cancer patients is not always simple, and conventional evaluation only has a limited value (23). The affected organs are identical to those observed in the African literature (13,14). In the study by Rosa et al, the highest incidence of AKI was observed in patients with cervical, ovarian and prostate cancers (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the potentially multifactorial complexity of anemia, defining causes in cancer patients is not always simple, and conventional evaluation only has a limited value (23). The affected organs are identical to those observed in the African literature (13,14). In the study by Rosa et al, the highest incidence of AKI was observed in patients with cervical, ovarian and prostate cancers (24).…”
Section: Discussionmentioning
confidence: 99%
“…The 4 most common cancers were, in order of frequency, breast, cervical, prostate and liver cancers (13). In Côte d'Ivoire, the most common cancers are breast cancer (25.7%), uterine cancer (24%), prostate cancer (15.8%) and liver cancer (15%) (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated incidence and mortality rates for the year 2020 are lower in Nigerian men (72.7/100,000) than women (76/100,000) (Parkin et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…Cervical cancer, the second most common cancer in Nigeria is mostly caused by an infection with Human Papilloma Virus (HPV) leading to invasive cancer 10-15 years after infection (Parkin et al, 2003). Other risk factors include: early commencement of intercourse, multiple sex partners, high parity, poverty, smoking and use of hormonal contraceptives (Kolawole, 2011).…”
Section: Introductionmentioning
confidence: 99%